(untitled) (Pedagogy of Higher and Secondary Education, 2003)
The necessity of professional and pedagogical research is substantiated activities in the context of society renewal and education reform. Methodological bases of the analysis of professional and pedagogical activity are considered. A significant place in the content of professional and pedagogical activities is given creativity. The main approach in the study is the activity approach. Prospects for further research are presented.